Bilobalide protection of normal human melanocytes from hydrogen peroxide‐induced oxidative damage via promotion of antioxidase expression and inhibition of endoplasmic reticulum stress. (14th July 2015) - Lu, L.; Wang, S.; Fu, L.; Liu, D.; Zhu, Y.; Xu, A.
Summary: Background: H2 O2 accumulating in the epidermis contributes to the melanocyte damage characteristic of vitiligo. Removal of H2 O2 by antioxidants is thus considered beneficial for patients with vitiligo. Aim: To investigate the protective effects and underlying mechanism of bilobalide, the main terpenoid constituent of Ginkgo biloba extract, against H2 O2 ‐induced oxidative damage in normal human melanocytes. Methods: Effects of bilobalide on melanocytes were investigated by measuring cell viability, heat shock protein (Hsp)70 release and levels of intracellular reactive oxygen species (ROS). Results: Pretreatment of melanocytes with bilobalide for 24 h significantly inhibited H2 O2 ‐induced apoptosis, Hsp70 release and intracellular ROS increase in a dose‐dependent manner. Bilobalide pretreatment increased the level of catalase (CAT) and glutathione peroxidase (GPx)1 mRNA in melanocytes. Although bilobalide moderately increased the phosphorylation of eukaryotic initiation factor 2, α subunit (eIF2α), suggesting its role in stimulating unfolded protein response signalling pathways, it also blocked the induction of anti‐C/EBP homologous protein expression by H2 O2 . Conclusion: This study indicates for the first time that bilobalide protects human melanocytes from oxidative damage by inhibiting H2 O2 ‐induced apoptosis and suppressing autoimmune response to melanocytes through reducing Hsp70 release. Instead of working as an ROS scavenger, bilobalide promotes the expression of antioxidases including CAT and GPx1, and inhibits H2 O2 ‐induced endoplasmic reticulum stress to protect melanocytes.